Elemental composition of suspended matter in the Scotia-Weddell Confluence area during spring and summer 1988 (EPOS leg 2) - Dehairs, Frank; Goeyens, Léo; Stroobants, N.; Mathot, Sylvie (1992)
During austral spring and summer 1988 the upper 500 m of water column in the Scotia-Weddell Confluence was sampled for the elemental composition of total suspended matter. For particulate organic carbon surface water concentrations ranged between 2.5 and 15 μmol/l, with an estimated 19 to 47% of this pool being detrital carbon. In late November, the highest surface water particulate organic carbon concentrations (15 μmol/l) occurred in the Confluence area where they coincided with a maximum in particulate Si (1.7 μmol/l). Later in the season particulate Si in the Confluence area decreased to ≤0.3 μmol/l. In the Scotia Sea on the contrary, surface water particulate Si increased with time and reached 3 μmol/l in late December. For particulate Ca and Sr in surface water, strong gradients are observed across the Scotia Front (e.g. Ca: from 230 to 10 nmol/l; Sr: from 1.0 to 0.1 nmol/l), with highest concentrations in the Scotia Sea. In general, these distributions are confirmed by the observations on plankton species composition, done by other participants. In the Scotia Sea heavily calcified coccolithophorids and diatoms occurred throughout the season, while in the Confluence area heavily calcified coccolithophorids were absent and a switch-over from diatom to naked flagellate dominance was observed following a krill event. In the surface waters, the lithogenic Si fraction represents on average only 4% of the total particulate Si content. However, this fraction reaches 60% below 100 m depth in the Confluence area, due mainly to the presence of a sub-surface maximum in the aluminosilicate load (particulate Al content up to 30 pmol/l), probably reflecting advection of resuspended shelf sediments. Subsurface Ba/barite concentrations are highest in the Scotia Sea (280 pmol/l) and decrease through the Scotia Front to reach values of 100 pmol/l and less in the Confluence area, the marginal ice zone and the closed pack ice zone. © 1992 Springer-Verlag. SCOPUS: ar.j info:eu-repo/semantics/published